Penerapan Nilai Pendidikan Karakter Dalam Pembelajaran Agama Hindu Di SMPN 5 Satap Randangan Desa Banuroja Kecamatan Randangan Kabupaten Puhuwato Provinsi Gorontalo - I Wayan Eka Pratama; I Nyoman Subagia; Ni Wayan Sri Prabawati Kusuma Dewi (Upadhyaya : Jurnal Penelitian Pendidikan, 2023)
Education is a process that occurs continuously which aims to change the identity of a student to be more advanced and develop in science. The cultivation of character values is very important for overcoming various problems of moral and behavioral deviations that occur in everyday life. This research method is a scientific way of obtaining data. These character values will be conveyed systematically and accepted by all groups, especially students as the nation's young generation. Character education as a form of implementing the dissemination of noble cultural values of the nation is a form of systematic, planned and measurable reinforcement. adhesive factor for social integration. Application of Character Education Values in Learning Hindu Religious Education at SMPN 5 Satap Randangan in Banuroja Village, Randangan District, Pohuwato Regency, Gorontalo Province. (1). What are the forms of character education values in learning Hinduism at SMPN 5 Satap Randangan, Banuroja village. (2). What are the obstacles to implementing character education values in learning Hinduism at SMPN 5 Satap Randangan, Banuroja village. (3). What are the efforts? the implementation of the application of character education values in learning Hinduism at SMPN 5 Satap Randangan, Banuroja Village, to Hindu students in general, especially for students at SMP 5 Satap, Banuroja Village, Randangan District, Pohuwato Regency, Gorontalo Province, it is hoped that it will be useful in relation to the application of values character education in learning Hindu Religion.